Analisis Strategi Pemasaran dan Preferensi Konsumen Pada Erista Griyo Dhahar Di Pakem Sleman Daerah Istimewa Yogyakarta - Khasnak Khanifah; Antik Suprihanti; Budiarto Budiarto (Agrisociabus, 2022)
This study aims to (1) analyze internal and external factors on Erista Griyo Dhahar (2) analyze the appropriate marketing strategy on Erista Griyo Dhahar (3) analyze consumer preferences for products, prices, locations, promotions, facilities and services at Erista Griyo Dhahar. The method used in this study is a quantitative research method with a case study approach. The method for determining respondents was purposive and accidental sampling. This study used primary data and secondary data. The method of data collection used were interviews, questionnaires, observation and documentation. Evaluating the instrument with validity and reliability tests. This study used SWOT analysis, QSPM and conjoint analysis. The results showed (1) Erista Griyo Dhahar's internal and external factors include strengths, weaknesses, opportunities and threats. The main strength is the unique flagship product that comes from the telang flower. The main Weakness is that the dining area is an open space and some are not permanent buildings. The main opportunity is to create a restaurant branch with a concept according to the target market. The main threat is there are restaurant competitors with a similar concept. (2) The marketing strategy for Erista Griyo Dhahar was an intensive strategy of intensively promoting via social media. (3) The most considered consumer preference is the price attribute and the most preferred combination of attribute levels is the combination of blue rice packages, low prices, location close to a home, promotions with discounted prices, facilities for a plants store, and responsive services.Keywords : Consumer preference, Conjoint, Marketing strategy, SWOT, QSPM.